(untitled) (Journal of Family Sciences, 2025)
Intimate Partner Violence (IPV) continues to receive global scholarly attention. Adult attachment theory provided a lens to understand IPV in close relationships. This study explored whether childhood attachment persists into adulthood, how insecure adult attachment relates to IPV risk, and what additional factors influence this across domestic and dating contexts as a form of IPV. A systematic literature review was conducted following PRISMA 2020 guidelines. Articles were retrieved from Scopus and Google Scholar using predefined keywords, focusing on studies published between 2015–2025. A total of 22 studies (N = 7211) met the eligibility criteria. The findings indicate while early attachment influence adult attachment, but the situational context and additional life experiences can shape the way individuals respond to their partner or the attached figure. In addition, the dynamics of the adult attachment, anxiety, and avoidance components are related to victims and perpetrators of violence. This review deepens the understanding of IPV through the adult attachment lens, emphasizing that attachment is not a fixed predictor. Future studies should examine other psychological and contextual factors and support the development of counselling and intervention strategies for IPV prevention.